The importance of the state military policy of the Central Rada in the modern development of the Ukrainian army. - Yaroslavna Volodymyrivna Viktorska (Czasopismo Prawno-Historyczne)
The article examines the scientific significance of the state military policy of the Central Council. It outlines the deployment of the military movement and the activities of the military bodies of the People's Republic of Ukraine. The significance and influence of the experience of the military policy of the Central Council for the present-day development of the state is delineated. Normative activity in the military sphere during the period of the Central Council and Independent Ukraine is analyzed. The issue of the legal, financial, and social situation of the military personnel of the Armed Forces between 1917 and 1919 is highlighted. The military legal norms of the period together with the military norms from the Independence of Ukraine are analyzed. The need to supplement these documents is proven, in particular by a detailed description of the role and function of the military personnel in the military formations as a component of military security policy. It is emphasized that the main priority in the national security system is the development, preservation, provision, and improvement of the regulatory and legal acts. The basic documents that defined the state policy of national security during the Central Council period as well as their significance for the present-day development of the Armed Forces of Ukraine are analyzed.